DEVELOPMENT OF PROFESSIONAL AND PEDAGOGICAL COMPETENCIES OF FUTURE HISTORY TEACHERS IN HISTORY EDUCATION BASED ON CLUSTER APPROACH - Toshtemirova, Saodat (Mental Enlightenment Scientific-Methodological Journal, 2024)
This research aims to analyze methods for developing the professional-pedagogical competencies of history teachers in higher education institutions using a cluster approach and to evaluate their impact on educational quality. Rapid changes and globalization in the modern education system necessitate the enhancement of teachers' professional qualifications. The findings demonstrate that the cluster approach effectively fosters various competencies in history teachers, including critical thinking, research, cognitive, communicative, problem-solving, digital, pedagogical-methodological, interdisciplinary, self-development, moral citizenship, tolerance, and creativity. Based on these results, new recommendations and models were proposed to improve education quality and develop teachers' competencies. These outcomes can inform policy making, teacher training programs, and serve as a foundation for future research in educational institutions.